A ação rescisória contra o título executivo que condena a Fazenda Pública: uma análise do art. 535, § 8º, do CPC/ 2015 - Martins, Fernando Motta (2024)
The objective of this work is to investigate the possible interpretation of art. 535, § 8º, of the Code of Civil Procedure, which allows the filing, by the Tax Authorities, of a peculiar hypothesis of an action for relief from judgment. In order to accomplish this task, we studied the principle of legal certainty, intending to identify the role that this principle play in legal-tax relations. In doing so, we deepened the study in relation to res judicata, unconstitutional res judicata and action for relief from judgment in tax matters, analyzing the main statements of the Federal Supreme Court regarding these topics. Finally, based on these guidelines, we indicate the interpretative limits of 535, § 8º, of the Code of Civil Procedure, imposed, in our view, by the constitutional text